A partial and multiple wavelet analysis of tourism and house prices. Issue 2 (3rd April 2022) - Wu, Tsung-Pao; Wu, Hung-Che; Liu, Shu-Bing; Hsueh, Shun-Jen; Chen, Junyan
ABSTRACT: This paper aims to examine the relationship between tourism activities and house prices (HP) in China's regions using wavelet transform context structures. The partial wavelet coherence (PWC) and multiple wavelet coherence (MWC) are applied to the available tourism data. Results indicate that there is a strong short-term comovement between tourism and its control variables at low, medium, and high frequencies between three tourism sectors in terms of PWC. As for MWC, tourism activities are generally highly correlated over time and frequency bands and become clear. In addition, the researchers uncover some differences between the comovement of control variables in tourism and their relationships through time and frequencies.